Предмет: Математика, автор: kondratuknikol07

срочно пожалуста дам 65 балов​

Приложения:

Ответы

Автор ответа: iramazurk
1

Пошаговое объяснение:

(а + 3) - (7 + 5а) = 2а + 32

а + 3 - 7 - 5а = 2а + 32

-4а - 4 = 2а + 32

-4а - 2а = 32 + 4

-6а = 36

а = 36 : (-6)

а = -6

36у + 6(у - 1) = -90

36у + 6у - 6 = -90

42у - 6 = -90

42у = -90 + 6

42у = -84

у = -84 : 42

у = -2

12(х + 5) = -24

12х + 60 = -24

12х = -24 - 60

12х = -84

х = -84 : 12

х = -7

3(6 - х) - 2(х - 5) = 63

18 - 3х - 2х + 10 = 63

-5х + 28 = 63

-5х = 63 - 28

-5х = 35

х = 35 : (-5)

х = -7

Похожие вопросы